Particle swarm optimization computer simulation of Ni clusters - 周继承 李文娟 朱金波 (Transactions of Nonferrous Metals Society of China, 2008)
The stable structures and energies of Ni clusters were investigated using particle swarm optimization（PSO） combined with simulated annealing（SA）. Sutton-Chen many-body potential was used in describing the interatomic interactions. The simulation results indicate that the structures of Ni clusters are icosahedral-like and binding energy per atom tends to approach that of bulk materials when the atoms number increases. The stability of Ni clusters depends not only on size but also on symmetrical characterization. The structure stability of Nin clusters increases with the increase of total atom number n. It is also found that there exists direct correlation between stability and geometrical structures of the clusters, and relatively higher symmetry clusters are more stable. From the results of the second difference in the binding energy, the clusters at n=3 is more stable than others, and the magic numbers effect is also found.